Surveillance of Colorectal Cancer (CRC) in Cystic Fibrosis (CF) Patients - Fabio Ingravalle; Giovanni Casella; Adriana Ingravalle; Claudio Monti; Federica De Salvatore; Domenico Stillitano; Vincenzo Villanacci (Gastrointestinal Disorders, 2021)
Cystic Fibrosis (CF) is the commonest inherited genetic disorder in Caucasians due to a mutation in the gene CFTR (Cystic Fibrosis Transmembrane Conductance Regulator), and it should be considered as an Inherited Colorectal Cancer (CRC) Syndrome. In the United States, physicians of CF Foundation established the “Developing Innovative Gastroenterology Speciality Training Program” to increase the research on CF in gastrointestinal and hepatobiliary diseases. The risk to develop a CRC is 5–10 times higher in CF patients than in the general population and even greater in CF patients receiving immunosuppressive therapy due to organ transplantation (30-fold increased risk relative to the general population). Colonoscopy should be considered the best screening for CRC in CF patients. The screening colonoscopy should be started at the age of 40 in CF patients and, if negative, a new colonoscopy should be performed every 5 years and every 3 years if adenomas are detected. For transplanted CF patients, the screening colonoscopy could be started at the age of 35, in transplanted patients at the age of 30 and, if before, at the age of 30. CF transplanted patients, between the age of 35 and 55, must repeat colonoscopy every 3 years. Our review draws attention towards the clinically relevant development of CRC in CF patients, and it may pave the way for further screenings and studies.